Clinical, Neurophysiological, Radiological, Pathological, and Genetic Features of Dysferlinopathy in Saudi Arabia - Alharbi, Norah; Matar, Rawan; Cupler, Edward; Al-Hindi, Hindi; Murad, Hatem; Alhomud, Iftteah; Monies, Dorota; Alshehri, Ali; Alyahya, Mossaed; Meyer, Brian; Bohlega, Saeed (Frontiers in Neuroscience, 2022)
Background: To characterize the phenotypic, neurophysiological, radiological, pathological, and genetic profile of 33 Saudi Arabian families with dysferlinopathy. Methods: A descriptive observational study was done on a cohort of 112 Saudi Arabian families with LGMD. Screening for the Dysferlin (DYSF) gene was done in a tertiary care referral hospital in Saudi Arabia. Clinical, Neurophysiological, Radiological, Pathological, and Genetic findings in subjects with dysferlin mutation were the primary outcome variables. Statistical analysis was done by Epi-info. Results: 33 out of 112 families (29.46%) registered in the LGMD cohort had Dysferlinopathy. 53 subjects (28 males, 52.83%) from 33 families were followed up for various periods ranging from 1 year to 28 years. The mean age of onset was 17.79 ± 3.48 years (Range 10 to 25 years). Miyoshi Myopathy phenotype was observed in 50.94 % (27 out of 53), LGMDR2 phenotype in 30.19% (16 out of 53), and proximodistal phenotype in 15.09% (8 out of 53) of the subjects. Loss of ambulation was observed in 39.62% (21 out of 53 subjects). Electrophysiological, Radiological, and histopathological changes were compatible with the diagnosis. Mean serum Creatinine Kinase was 6464.45 ± 4149.24 with a range from 302 to 21483 IU/L. In addition, 13 dysferlin mutations were identified two of them were compound heterozygous. One founder mutation was observed c.164_165insA in 19 unrelated families. Conclusion: The prevalence of Dysferlinopathy was 29.46% in the native Saudi LGMD cohort. It is the most prevalent subtype seconded by calpainopathy. The clinical course varied among the study subjects and was consistent with those reported from different ethnic groups. One founder mutation was identified. Initial screening of the founder mutations in new families is highly recommended.